2004
DOI: 10.1002/sim.1877
|View full text |Cite
|
Sign up to set email alerts
|

Two‐stage adaptive strategy for superiority and non‐inferiority hypotheses in active controlled clinical trials

Abstract: In active controlled trials without a placebo arm, there are usually two study objectives: to test a superiority hypothesis that the experimental treatment is more effective than the active control therapy, and to test a non-inferiority hypothesis that the experimental treatment is therapeutically no worse than the active control within a defined margin. For a two-stage adaptive design, it is not necessary to give a fixed sample size calculation at the planning stage of the study when treatment effect informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The calculation of the phase 2 sample size was based on a stopping for futility approach, 23,24 assuming that the actual phase 2 trial represented an interim analysis of a (hypothetical) phase 3 trial. The test decision (with respect to phase 2) was made by looking at the conditional power that volasertib would show superiority in the hypothetical phase 3 trial.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The calculation of the phase 2 sample size was based on a stopping for futility approach, 23,24 assuming that the actual phase 2 trial represented an interim analysis of a (hypothetical) phase 3 trial. The test decision (with respect to phase 2) was made by looking at the conditional power that volasertib would show superiority in the hypothetical phase 3 trial.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Similar two-stage adaptive designs but with a less speciÿc procedure for determining the second-stage sample size were also considered by Brannath et al [16]. The focus of References [1,13,15,16] has been on how to maintain the overall type I error at a prescribed level in an adaptive design that allows mid-course switch between the superiority and noninferiority hypotheses. Although we have not mentioned it explicitly when we introduce our group sequential tests in Section 3, our goal has been to develop e cient tests that have the prescribed type I error probability.…”
Section: Discussionmentioning
confidence: 96%
“…Reference [9,Chapter 7], [14]). To circumvent the di culties for time-to-event endpoints in the group sequential approach with error spending functions, Shih et al [15] recently proposed to use a two-stage adaptive design instead of the more e cient group sequential strategy of Wang et al [1] for choosing between the superiority and non-inferiority objectives. Similar two-stage adaptive designs but with a less speciÿc procedure for determining the second-stage sample size were also considered by Brannath et al [16].…”
Section: Discussionmentioning
confidence: 99%
“…Shih et al [17] showed that when n 2 (u) is a non-increasing function of u, p(t, δ 0 ) expressed by (7) is an increasing function of δ 0 and also p(t, −∞) = 0 and p(t, ∞) = 1 for all finite t. Therefore, the lower bound of the (1 − α)100% one-sided C.I. can be found by solving the equation p(t, δ 0 ) = α.…”
Section: Estimation Following the Lsw Likelihood Methodsmentioning
confidence: 98%